The appearance and modulation of osteocyte marker expression during calcification of vascular smooth muscle cells. - Dongxing Zhu; Neil Charles Wallace Mackenzie; José Luis Millán; Colin Farquharson; Vicky Elizabeth MacRae (PLoS ONE)
Background Vascular calcification is an indicator of elevated cardiovascular risk. Vascular smooth muscle cells (VSMCs), the predominant cell type involved in medial vascular calcification, can undergo phenotypic transition to both osteoblastic and chondrocytic cells within a calcifying environment. Methodology/principal findings In the present study, using in vitro VSMC calcification studies in conjunction with ex vivo analyses of a mouse model of medial calcification, we show that vascular calcification is also associated with the expression of osteocyte phenotype markers. As controls, the terminal differentiation of murine calvarial osteoblasts into osteocytes was induced in vitro in the presence of calcifying medium (containing ß-glycerophosphate and ascorbic acid), as determined by increased expression of the osteocyte markers DMP-1, E11 and sclerostin. Culture of murine aortic VSMCs under identical conditions confirmed that the calcification of these cells can also be induced in similar calcifying medium. Calcified VSMCs had increased alkaline phosphatase activity and PiT-1 expression, which are recognized markers of vascular calcification. Expression of DMP-1, E11 and sclerostin was up-regulated during VSMC calcification in vitro. Increased protein expression of E11, an early osteocyte marker, and sclerostin, expressed by more mature osteocytes was also observed in the calcified media of Enpp1(-/-) mouse aortic tissue. Conclusions/significance This study has demonstrated the up-regulation of key osteocytic molecules during the vascular calcification process. A fuller understanding of the functional role of osteocyte formation and specifically sclerostin and E11 expression in the vascular calcification process may identify novel potential therapeutic strategies for clinical intervention.